Spirulina Culture in Bangladesh XI: Selection of a Culture Medium, Suitable for Culturing a Local Strain of Spirulina (Bangladesh Journal of Scientific and Industrial Research, 2007)
Large scale Spirulina culture is possible in Bangladesh inspite of unpredictable climatic condition. Effect of different culture media on the growth of a local strain of Spirulina (Spirulina platensis) was studied. Bangladesh medium (Bd1) was found to be more favourable for the growth of the alga. All together three culture media were included in this study. Bangladesh J. Sci. Ind. Res. 41(3-4), 227-234, 2006